The Palaearctic genus Belothrips Haliday (Thysanoptera: Thripidae), with new synonyms and new combinations - Mirab-Balou, Majid; Mound, Laurence; Goldarazena, Arturo; Negi̇ş İnci Şahi̇n (Zootaxa, 2025)
The two genera, Nigritothrips Bhatti and Rubiothrips Schliephake are placed as new synonyms of Belothrips Haliday. Belothrips acuminatus, the type species of this genus, is considered in detail to include Rubiothrips parisae Mirab-balou & Chen as a new synonym. The species Nigritothrips zurstrasseni Bhatti is considered a new synonym of Belothrips longistylosus Priesner. A checklist is provided of the 12 species now included in Belothrips, indicating two new combinations and eight revised combinations. The genus Belothrips is newly recorded for the fauna of both China and Iran.